The gut hormone receptor GIPR links energy availability to the control of hematopoiesis - Gemma Pujadas; Elodie M. Varin; Laurie L. Baggio; Erin E. Mulvihill; K.W.Annie Bang; Jacqueline A. Koehler; Dianne Matthews; Daniel J. Drucker (Elsevier, 2020)
Objective: Glucose-dependent insulinotropic polypeptide (GIP) conveys information from ingested nutrients to peripheral tissues, signaling energy availability. The GIP Receptor (GIPR) is also expressed in the bone marrow, notably in cells of the myeloid lineage. However, the importance of gain and loss of GIPR signaling for diverse hematopoietic responses remains unclear. Methods: We assessed the expression of the Gipr in bone marrow (BM) lineages and examined functional roles for the GIPR in control of hematopoiesis. Bone marrow responses were studied in (i) mice fed regular or energy-rich diets, (ii) mice treated with hematopoietic stressors including acute 5-fluorouracil (5-FU), pamsaccharide (LPS), and Pam3CysSerLys4 (Pam3CSK4), with or without pharmacological administration of a GIPR agonist, and (iii) mice with global (Gipr−/−) or selective deletion of the GIPR (GiprTie2−/−) with and without bone marrow transplantation (BMT). Results: Gipr is expressed within T cells, myeloid cells, and myeloid precursors; however, these cell populations were not different in peripheral blood, spleen, or BM of Gipr−/− and GiprTie2−/− mice. Nevertheless, gain and loss of function studies revealed that GIPR signaling controls the expression of BM Toll-like receptor (TLR) and Notch-related genes regulating hematopoiesis. Loss of the BM GIPR attenuates the extent of adipose tissue inflammation and dysregulates the hematopoietic response to BMT. GIPR agonism modified BM gene expression profiles following 5-FU and Pam3CSK4 whereas loss of the Gipr altered the hematopoietic responses to energy excess, two TLR ligands, and 5-FU. However, the magnitude of the cellular changes in hematopoiesis in response to gain or loss of GIPR signaling was relatively modest. Conclusion: These studies identify a functional gut hormone-BM axis positioned for the transduction of signals linking nutrient availability to the control of TLR and Notch genes regulating hematopoiesis. Nevertheless, stimulation or loss of GIPR signaling has minimal impact on basal hematopoiesis or the physiological response to hematopoietic stress.